2019
DOI: 10.1021/acsami.8b19645
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Two-Dimensional Flux Pinning Centers in MgB2 Superconductors Induced by Graphene-Coated Boron

Abstract: Extrinsic two-dimensional flux pinning centers, via graphene-encapsulated boron powder as precursors, have been introduced into MgB2 superconductors by means of in situ and diffusion sintering methods. Uniform graphene encapsulation of the boron powders was achieved by the hydrothermal method with highly dispersed graphene oxide as the precursor. The graphene coating layers induce remaining graphene layers and other defects acting as flux pinning centers in the matrix as well as improved connectivity in betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 72 publications
2
16
0
Order By: Relevance
“…Their studies revealed the homogeneous graphene coating in the microstructure and also similar irreversibility field values. [42] Based on the abovementioned discussion, we can conclude that the present results represent an optimized scenario with improved superconducting performance of bulk MgB 2 , while maintaining the uniform carbon doping and high T c when compared with other carbon doping techniques.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Their studies revealed the homogeneous graphene coating in the microstructure and also similar irreversibility field values. [42] Based on the abovementioned discussion, we can conclude that the present results represent an optimized scenario with improved superconducting performance of bulk MgB 2 , while maintaining the uniform carbon doping and high T c when compared with other carbon doping techniques.…”
Section: Resultssupporting
confidence: 64%
“…Their studies revealed the homogeneous graphene coating in the microstructure and also similar irreversibility field values. [ 42 ]…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [103] have fabricated MgB 2 by the boron particles with a graphene coating via in situ method, hydrothermal process, successfully induced 2D flux pinning centers and achieved optimized graphene distribution. And the MgB 2 bulks fabricated by the in situ (iG−x) and diffusion (dG−x) methods were compared to study the connectivity and flux pinning effect.…”
Section: Two-dimensional Flux Pinning Centersmentioning
confidence: 99%
“…As one of the largest commercial applications of a superconductor, liquid helium (LHe)-cooled niobium–titanium (Nb–Ti)-based superconducting magnets are routinely used in magnetic resonance imaging (MRI) to produce a strong, uniform, and ultrastable magnetic field for obtaining high-resolution images . In recent times, however, there has been a shortage of helium gas, so that its price is also continuously increasing. Magnesium diboride (MgB 2 ) conductors are known to be a good choice for LHe-free MRI magnet applications to minimize reliance on LHe. , …”
Section: Introductionmentioning
confidence: 99%